1995
DOI: 10.1007/bf01464339
|View full text |Cite
|
Sign up to set email alerts
|

Interphase in situ hybridization to disaggregated and intact tissue specimens of prostatic adenocarcinomas

Abstract: A comparative study was performed of interphase in situ hybridization (ISH) to deparaffinized 4-gm tissue sections and nuclear suspensions from eight prostatic adenocarcinomas, as well as one normal prostatic control. Whole nuclear suspensions were derived from the same tumor areas to evaluate differences of ISH to truncated versus whole nuclei. DNA probes specific for the centromeres of chromosome l, 7, 8, 10, and Y were used for detection of numerical chromosomal changes and aneuploidy. In six adenocarcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…CISH analysis was performed as previously described by Alers et al 25 CISH probes were labelled with fluorescein (Amersham Pharmacia), by random priming, as described above. Probe detection was performed using horseradish peroxidase antifluorescein (Roche) and H 2 O 2 -diaminobenzidine.…”
Section: Cish Analysismentioning
confidence: 99%
“…CISH analysis was performed as previously described by Alers et al 25 CISH probes were labelled with fluorescein (Amersham Pharmacia), by random priming, as described above. Probe detection was performed using horseradish peroxidase antifluorescein (Roche) and H 2 O 2 -diaminobenzidine.…”
Section: Cish Analysismentioning
confidence: 99%
“…A more detailed description of the probes used is given in refs 17, 25, and refs cited therein. Selection criteria were based on previous studies 16,17 and other literature data considering cytogenetic aberrations in prostatic tumours. 8,9,21,22 The (peri)centromeric repetitive satellite DNA probes were labelled with biotin-14-dATP by nick translation of complete plasmid DNA according to the manufacturer's directions (BRL, Gaithersburg, MD, U.S.A.).…”
Section: Probe Set and Probe Labellingmentioning
confidence: 99%
“…A CGH study 15 performed on regional lymph node and bone metastases showed frequent gain of 8q, as well as loss of 8p, 10q, 13q, 16q and 17p sequences in over half of cases. Interphase in situ hybridization (ISH) to nuclear suspensions, touch preparations, and paraffin sections of both prostatic tumours and precursor lesions (PIN) revealed numerical aberrations of chromosomes 7, 8, 10, 16, 17, 18, X, and Y, [16][17][18][19] as well as loss of sequences in the 8p12-p22 region. 20 Furthermore, fluorescent ISH (FISH) studies of nuclear suspensions or touch imprints of mostly primary prostatic tumours suggested that alterations of chromosome 7 and/or 8 may be prognostic markers predicting unfavourable outcomes in prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…From these sections, the corresponding tumor areas were selectively cut out with a fine scalpel under microscopic control. For disaggregation of tumor nuclei, the protocol of Alers et al (1995a) was modified. Briefly, after deparaffination and rehydration, samples were digested in a pronase E solution (0.05% in phosphatebuffered saline, PBS, pH 7.0) for 2 h at 37°C, with vigorous vortexing every 15 min.…”
Section: Patients and Tumor Samplesmentioning
confidence: 99%
“…Several studies have demonstrated the reliability of this technique for an evaluation of numerical chromosome aberrations (Alers et al 1995a;Bandyk et al 1994;Herrington et al 1995;Micale et al 1992). To enable a correlation of FISH analysis and histomorphological patterns, the method was modified for its application on routine paraffin-embedded tissue sections (van Dekken et al 1992;Dhingra et al 1994;Hopman et al 1991;Kim et al 1993).…”
Section: Introductionmentioning
confidence: 99%